Pengaruh Indeks Harga Saham Global terhadap Indeks Harga Saham Indonesia Studi Kasus Sebelum dan Selama Periode Covid- 19 - Ricky Martin Simanullang; Roy Sembel; posma Sariguna Johnson Kennedy; Rutman Lumbantoruan; Suzanna Josephine Tobing (IKRAITH-EKONOMIKA, 2023)
This study was conducted to examine the effect of the five largest stock price indices in the world on the Indonesian Composite Stock Price Index in the time series before the COVID-19pandemic and during the COVID-19 pandemic, taken from January 1, 2015 June 30, 2022. This study uses the stepwise regression method. The results in this study indicate that in the period before the COVID-19 pandemic the variables that affected the IHSG were the New York Stock Exchange and Euronext N.V, each of which had a positive effect, while during the COVID-19pandemic the variables that affected the IHSG were New York Stocks. Exchange, Nasdaq Stock Market, Shanghai Stock Exchange, and Euronext N.V with the results of the New York Stock Exchange and Shanghai Stock Exchange having a positive effect, Nasdaq Stock Market and Euronext N.V having a negative effect.